A portrait of the artist as a young man - Joyce, James, 1882-1941 (The Modern Library of the world's best books, 1928)
A Portrait of the Artist as a Young Man tells the story of Stephen Dedalus, a boy growing up in Ireland at the end of the nineteenth century, as he gradually decides to cast off all his social, familial, and religious constraints to live a life devoted to the art of writing. As a young boy, Stephen's Catholic faith and Irish nationality heavily influence him. He attends a strict religious boarding school called Clongowes Wood College. At first, Stephen is lonely and homesick at the school, but as time passes he finds his place among the other boys. He enjoys his visits home, even though family tensions run high after the death of the Irish political leader Charles Stewart Parnell. This sensitive subject becomes the topic of a furious, politically charged argument over the family's Christmas dinner. Stephen's father, Simon, is inept with money, and the family sinks deeper and deeper into debt. After a summer spent in the company of his Uncle Charles, Stephen learns that the family cannot afford to send him back to Clongowes, and that they will instead move to Dublin. Stephen starts attending a prestigious day school called Belvedere, where he grows to excel as a writer and as an actor in the student theater. His first sexual experience, with a young Dublin prostitute, unleashes a storm of guilt and shame in Stephen, as he tries to reconcile his physical desires with the stern Catholic morality of his surroundings. For a while, he ignores his religious upbringing, throwing himself with debauched abandon into a variety of sins-masturbation, gluttony, and more visits to prostitutes, among others. Then, on a three-day religious retreat, Stephen hears a trio of fiery sermons about sin, judgment, and hell. Deeply shaken, the young man resolves to rededicate himself to a life of Christian piety. Stephen begins attending Mass every day, becoming a model of Catholic piety, abstinence, and self-denial. His religious devotion is so pronounced that the director of his school asks him to consider entering the priesthood. After briefly considering the offer, Stephen realizes that the austerity of the priestly life is utterly incompatible with his love for sensual beauty. That day, Stephen learns from his sister that the family will be moving, once again for financial reasons. Anxiously awaiting news about his acceptance to the university, Stephen goes for a walk on the beach, where he observes a young girl wading in the tide. He is struck by her beauty, and realizes, in a moment of epiphany, that the love and desire of beauty should not be a source of shame. Stephen resolves to live his life to the fullest, and vows not to be constrained by the boundaries of his family, his nation, and his religion. Stephen moves on to the university, where he develops a number of strong friendships, and is especially close with a young man named Cranly. In a series of conversations with his companions, Stephen works to formulate his theories about art. While he is dependent on his friends as listeners, he is also determined to create an independent existence, liberated from the expectations of friends and family. He becomes more and more determined to free himself from all limiting pressures, and eventually decides to leave Ireland to escape them. Like his namesake, the mythical Daedalus, Stephen hopes to build himself wings on which he can fly above all obstacles and achieve a life as an artist.